Power quality enhancement of grid-connected PV system - Debani Prasad Mishra; Kshirod Kumar Rout; Sivkumar Mishra; Mandakurit Nivas; Rambilli Krishna Prasad Rao Naidu; Surender Reddy Salkuti (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Solar photovoltaic (PV) power, for its multiple benefits, has adhered to prominent consideration in the electrical energy generation region. The double-stage triple-phase grid-connected solar PV (SPV) system is utilized to enhance the power quality by employing a lymphoblastoid cell lines LCL filter. In this method, a DC-DC converter and DC-AC converter make a feasible juncture of the PV systems to the electrical interface. For converting boosted DC into AC, A 3-phase DC-AC converter is used, which is supplied into the grid. A 3-phase voltage converter is employed in place of an inverter for interfacing amid the voltage generated by the PV system and the grid possessing an AC transmission line. An maximum power point tracking (MPPT) application is used in this proposal to amplify the effectiveness of the PV array in face of any unsteady climatic circumstances. Hence, the highest energy could be secured out of the solar PV array and interfaced with the grid. Enhancing power quality by employing an LCL filter is quantified by FFT analysis in MATLAB. The advised proposal has attained a very low total harmonic distortion (THD), proving its efficacy. Also, the outcomes ascertain the applications of the proposed system and extend future advances of renewable energy with a great power quality improvement.